Directed Growth of Dendritic Polymer Networks for Organic Electrochemical Transistors and Artificial Synapses. (2nd August 2021) - Cucchi, Matteo; Kleemann, Hans; Tseng, Hsin; Ciccone, Giuseppe; Lee, Alexander; Pohl, Darius; Leo, Karl
Abstract: Organic electrochemical transistors (OECTs) are an emerging class of devices which operate in electrolytic solution and show controllable memory effects. For these reasons, OECT hold great potential for applications in bioelectronics and neuromorphic computing. Among the methods proposed to fabricate OECT channels, electropolymerization stands out because it allows to produce electrical connections on the substrates on‐demand and further modify them to adjust their electrical properties to meet circuit requirements. However, the practical application of this method is hampered by the difficulty in controlling the growth direction as well as the morphology of the film, resulting in a large device‐to‐device variability and limiting the down‐scaling of the devices. In this study, AC‐electropolymerization is proposed to produce directionally controlled channels. The method allows to adjust physical properties such as resistance and capacitance by varying the polymerization parameters, such as voltage, frequency, and salt concentration. The growth mechanism, material morphology, and network topology is investigated, and the advantages of this approach by showing tunable neuromorphic features and the possibility to scale down the channels to the micrometer scale is demonstrated. Abstract : Polymeric dendritic networks are proposed as building blocks for neuromorphic computing. In this work, we use AC electropolymerization to direct the growth of conductive networks and tune their capacitance and resistance. Moreover, important neuromorphic features such as STDP, depression, potentiation and Pavlovian learning can be emulated with this technique.